PAS10 is a tetratricopeptide-repeat protein that is essential for the import of most matrix proteins into peroxisomes of Saccharomyces cerevisiae. - Van der Leij, I (1993)
pas mutants of Saccharomyces cerevisiae are disturbed in peroxisome assembly (pas) and proliferation. Here we report the characterization of the PAS10 gene and its product (PAS10) that is essential for the import of a large subset of proteins into the peroxisomal matrix. PAS10, a protein of 69 kDa, is a member of the tetratricopeptide repeat, or snap helix, protein family, characterized by several direct repeats of a degenerate 34-amino acid motif (Sikorski, R. S., Boguski, M. S., Goebl, M. & Hieter, P. (1990) Cell 60, 307-317). Other members of this family are MAS70 (S. cerevisiae) and MOM72 (Neurospora crassa), which are mitochondrial receptors for protein import. A pas10 null mutant accumulates peroxisomal, leaflet-like membrane structures and exhibits deficient import of a number of peroxisomal matrix enzymes, particularly of proteins with an SKL-like import signal. In contrast, 3-ketoacyl-CoA thiolase associated with these membranes is resistant in vitro to degradation by proteinase K, indicating true protein import. These results suggest that PAS10 is an essential component of a peroxisomal import machinery which mediates the translocation of a specific subset of proteins to the peroxisomal matrix with an SKL-like import signal.